Transoral Fully Robotic Dissection of a Parapharyngeal Hemangioma. Issue 7 (October 2016) - Granell, Jose; Alonso, Ana; Garrido, Laura; Gutierrez-Fonseca, Raimundo
Abstract : Abstract: Soft tissue robotics found its trigger for success in minimally invasive surgery. The minimization of the surgical damage is more obvious as the surgical alternative is more aggressive. In head and neck surgery, potential sequelae are both functional and cosmetic. Robotic instrumentation might allow for further development of the transoral approach to the deep regions of the face. The authors present an uneventful, fully robotic, transoral surgical excision of a parapharyngeal hemangioma. The authors discuss management alternatives, surgical risks, and safety measures. The medial approach is the natural choice, provided it is safe and technically feasible. Transoral robotic surgery could be a reasonable minimally invasive approach for selected parapharyngeal tumors. Abstract : Supplemental Digital Content is available in the text